The Use of Stamp Games to Improve Addition and Subtraction Skills in Students with Mild Intellectual Disability: Single Subject Research - Galuh Tri Nugraheni; Sri Tirto Madawistama; Eko Yulianto (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
This study aimed to determine the effectiveness of the stamp game in improving addition and subtraction skills of a student with an intelligence quotient (IQ) score of 50, categorized Mild Intellectual Disability. The research employed a quantitative descriptive method using a Single Subject Research (SSR) experimental approach. The study applied a reversal A-B-A design consisting of Baseline -1 (A1), intervention (B), Baseline -2 (A2) phases. Data were collected through tests, observation, and interviews. The participant was an eighth-grade student at an inclusive public junior high school in Tasikmalaya, selected through purposive sampling. Data were analyzed using visual graphical analysis within and between conditions across 18 sessions the findings showed an increase in the mean level from 7.42% in Baseline-1 (A1) to 63.43% during the intervention phase and further increased to 85.25% in Baseline-2 (A2). Data stability reached at least 85% within conditions and remained stable across conditions. The level change increased by 57% from Baseline-1 (A1) to intervention and by 20% from intervention to Baseline-2. The overlap percentage was 0%, indicating no data overlap. These results suggest that the Stamp Game is Effective in improving addition and subtraction skills in students with mild intellectual disability the improvement was maintained during the Baseline-2 (A2) phase, indicating that the effect persisted even after the intervention was withdrawn.